Financial Management in the Context of Globalization: A Bibliometric Study - Bagas Wibowo; Christian Edyanto; Rakha Satrio; Rohana Aini; Muhammad Ramadhani Kesuma (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This research analyzes the growth of research on financial management in the age of globalization using Scopus from the years 2000 to 2024. There is an evident growth in the number of publications in congressed performance data and the results show the years after 2017 are especially due to worldwide digital shocks and the increased emphasis on sustainable development. Using science-mapping techniques, the analysis identifies the major concepts of globalization and finance and the emerging subthemes of the green finance, risk management, innovation, and supply-chain finance, as well as the post-COVID transformations. The changes within the subfields and the governance and digital and environmental changes are illustrated in the co-occurrence and word cloud structures of documents. Data from co-citation clustering point to the primary knowledge base of the subfield to be institutional theory, network society and global production systems in the literature, and critical political economy. The sheer volume of the knowledge shows the interdisciplinary and expanding contour of research on the crossing of globalization and the management of finance. The study has resulted in a synthesized knowledge of the most notable contributions, and the more comprehensive thematic areas and untapped areas, which is beneficial to academia, to practice, and to governance, and finance on a global scale.